Electromyographic analysis of the stomatognathic system of children with Molar-incisor hypomineralization - Milena Rodrigues Carvalho; Simone Cecilio Hallak Regalo; Selma Siéssere; Lígia Maria Napolitano Gonçalves; Francisco Wanderley Garcia de Paula-Silva; Fernanda Vicioni-Marques; Paulo Nelson-Filho; Paulo Batista de Vasconcelos; Fabrício Kitazono de Carvalho; Alexandra Mussolino de Queiroz (PLoS ONE, 2023)
Introduction Molar-incisor hypomineralization (MIH) is a qualitative defect of dental enamel that affects one or more permanent first molars, with or without involvement of the incisor teeth. This condition leads to challenges to dental care and treatment planning. Aim Based on the hypothesis that children who have MIH possibly present alterations in postural and masticatory activities and considering the absence of studies investigating these parameters, the present study evaluated the functionality of the stomatognathic system considering the mentioned aspects. Materials The comparison of individuals with (MIHG; n = 32) and without MIH (CG; n = 32) was evaluated by electromyographic activity of the masseter and temporal muscles (right and left), as well as evaluation of the masticatory cycles during habitual mastication. Results MIHG showed muscle hyperactivity in postural and dynamic conditions compared to the CG; higher electromyographic values for MIHG when compared to CG in the following postural conditions: at rest for the right temporal (p = 0.00) and left temporal muscles (p = 0.03); in the protrusion to the right temporal muscle (p = 0.02); in the right laterality for the right masseter (p = 0.00) and left temporal muscles (p = 0.01); in the left laterality for the right masseter (p = 0.03) and left temporal (p = 0.04) muscles. In dynamic conditions with consistent food, significance was observed for the left temporal (p = 0.01); and with soft food for the right (p = 0.01) and left temporal muscles (p = 0.04). Conclusions Children with MIH seem to have impaired functionality of the stomatognathic system. Children with MIH have alterations in the stomatognathic system.